Slums and Human security/A Field social study in slums in the city of Baghdad: - Nouran Mahdi Abas, Ass.Prof .Dr; Maysam Yaseen Obaid, Asst.prof.Dr. (lark, 2022)
Current study objective is to know the concept of human populations secure in which provided for individuals in the slums regions. The study performed in Baghdad city, in slums on both sides of Al-Karkh and Al-Rusafa exactly; for the objective to know the fact of human security and services which available for whom reside in these regions, and the most important needs and challenges faced by individuals. To achieve that, the researcher followed the descriptive analytical method, in which approach by applying a questionnaire to an intentional sample of (350) individuals (persons) residing in slums regions in city of Baghdad on both sides, beside following the social survey method in a sampling method, as well as using data collection tools, which are questionnaire, observation, and interview. The results of study obvious that the lack of health services submitted to this individuals in the selected regions randomness at a rate of (98.6%), and that the reason for the study sample’s residence in random areas is the weak economic situation at a rate of (38.6%), and that there are needs that our study sample lacks within the random areas at a rate of (99.7%).